Explorasi Estetika dan Teknik Penciptaan Patung Dewi Saraswati Berbahan Beton - Okatama, Wayan; Ngidep Wiyasa, I Nyoman; Laba, I Nyoman (Pusat Penerbitan LPPM ISI Bali, 2025)
Sculpture is a form of three-dimensional visual expression that not only emphasizes aesthetic value but also embodies profound symbolic and spiritual meanings. In Balinese cultural tradition, the statue of Dewi Saraswati holds significant importance as a religious symbol representing knowledge, wisdom, and purity. These values have been passed down from generation to generation, making the statue not merely a work of art but also an integral part of religious practice and spiritual life. Therefore, the exploration of the creation of the Dewi Saraswati statue is considered relevant, particularly in the context of expanding artistic practices to other regions, such as South Lampung Regency. This exploration focuses on both the aesthetic aspects and technical processes involved in creating the statue using concrete as the primary material. Concrete is chosen for its durability, malleability, and strong visual expression. South Lampung is regarded as having great potential, both in terms of raw material availability and the local Hindu community’s demand for religious statues as decorative and symbolic elements in worship spaces and residential environments. The creation process adopts the